Utilitarian Policy of Criminalization for the COVID-19 Vaccine Refusal in Indonesia - Kurniawan, Kukuh Dwi; Bachtiar, Hasnan; Al-Fatih, Sholahuddin (Jurnal Media Hukum, 2000)
This article aims to analyze several issues of the implementation of the regulation of vaccination in Indonesia, encompassing the issues of the imposition of criminalization following the vaccination refusal, discussion on its objective, and practical challenges that potentially emerge. As qualitative research, this article employed a normative legal approach and social contextualization to comprehend regulations, legal interpretations, and arguments. This article finds that the government has amended the Presidential Regulation No. 99 of 2020 on the Procurement and Implementation of Vaccination to the Presidential Regulation No. 14 of 2021 on the Change of the Presidential Regulation No. 99 of 2020 in dealing with the issue of punishment imposed on those refusing the vaccination. From the perspective of utilitarian humanism, the regulation aims to ensure the success of the vaccination and is expected to result in the herd immunity of society that determines the social welfare in the country. The implementation of the regulation is being criticized on the practical level because it is claimed to raise the likelihood of the violation of human rights and overlook the public trust on account of excessive criminalization. This article argues that support from society is vital in the implementation of the regulation, while a positive campaign over public vaccinations need to be massively urged.